Protection of Human Rights in Freedom of Opinion and Expression on Social Media - Nizam Tazmi (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Freedom of opinion and expression is a universally recognized human right, including in the context of social media. However, the development of digital technology and social media has created new challenges regarding the limitation and protection of this right. This article aims to examine the protection of human rights to freedom of opinion and expression on social media and to identify legitimate limitations under international and national legal frameworks. Using a normative legal approach, this study highlights applicable legal principles and relevant regulations at the national level. The results of the study indicate that although freedom of expression is guaranteed, measures are needed to protect public interests, such as national security, public reporting, and the rights of others. It is recommended that governments and social media platforms adopt a balanced policy in managing content, in order to protect freedom of expression without neglecting the rights and safety of other users.